The impact and cost-effectiveness of nonavalent HPV vaccination in the United States: Estimates from a simplified transmission model. Issue 6 (2nd June 2016) - Chesson, Harrell W.; Markowitz, Lauri E.; Hariri, Susan; Ekwueme, Donatus U.; Saraiya, Mona
ABSTRACT: Introduction : The objective of this study was to assess the incremental costs and benefits of the 9-valent HPV vaccine (9vHPV) compared with the quadrivalent HPV vaccine (4vHPV). Like 4vHPV, 9vHPV protects against HPV types 6, 11, 16, and 18. 9vHPV also protects against 5 additional HPV types 31, 33, 45, 52, and 58.Methods : We adapted a previously published model of the impact and cost-effectiveness of 4vHPV to include the 5 additional HPV types in 9vHPV. The vaccine strategies we examined were (1) 4vHPV for males and females; (2) 9vHPV for females and 4vHPV for males; and (3) 9vHPV for males and females. In the base case, 9vHPV cost $13 more per dose than 4vHPV, based on available vaccine price information.Results : Providing 9vHPV to females compared with 4vHPV for females (assuming 4vHPV for males in both scenarios) was cost-saving regardless of whether or not cross-protection for 4vHPV was assumed. The cost per quality-adjusted life year (QALY) gained by 9vHPV for both sexes (compared with 4vHPV for both sexes) was < $0 (cost-saving) when assuming no cross-protection for 4vHPV and $8, 600 when assuming cross-protection for 4vHPV.Conclusions : Compared with a vaccination program of 4vHPV for both sexes, a vaccination program of 9vHPV for both sexes can improve health outcomes and can be cost-saving.